Stressors, Appraisal of Stressors, Experienced Stress and Cardiac Response: A Real-Time, Real-Life Investigation of Work Stress in Nurses. Issue 2 (25th November 2015) - Johnston, Derek; Bell, Cheryl; Jones, Martyn; Farquharson, Barbara; Allan, Julia; Schofield, Patricia; Ricketts, Ian; Johnston, Marie
Abstract: Background: Stress in health care professionals may reflect both the work and appraisal of work and impacts on the individuals, their patients, colleagues and managers. Purpose: The purpose of the present study is to examine physiological and psychological effects of stressors (tasks) and theory-based perceptions of work stressors within and between nurses in real time. Methods: During two work shifts, 100 nurses rated experienced stress, affect, fatigue, theory-based measures of work stress and nursing tasks on electronic diaries every 90 min, whereas heart rate and activity were measured continuously. Results: Heart rate was associated with both demand and effort. Experienced stress was related to demand, control, effort and reward. Effort and reward interacted as predicted (but only within people). Results were unchanged when allowance was made for work tasks. Conclusions: Real-time appraisals were more important than actual tasks in predicting both psychological and physiological correlates of stress. At times when effort was high, perceived reward reduced stress.